Design and Validation of a Scale of Core Components of Community Interventions in Mental Health - Rojas-Andrade, R (John Wiley and Sons Ltd, 2024)
Aims: To develop and validate an instrument to identify the core components of community strategies for mental health, especially mutual aid groups: The Mutual Aid Scale. Methods: 135 community strategies leaders participated in the study. The core components are active agency, coping strategies, recognition, and management of emotions, problem-solving strategies, supportive interaction, trust, self-identity construction, and strengthening of social networks. With these components a scale was designed. Content validity was carried out in addition to an exploratory factor analysis. Results: Two dimensions resulted, strengthening of agency capacity and Coping strategies, and the internal consistency of both factors was acceptable, with a Cronbach s alpha of 0.722 and 0.727, respectively. The Kaiser-Meyer-Olkin (KMO) statistic was used with a score of 0.831 and the Barlett Sphericity Test, with a significant value of 265.175. Conclusion: This scale identifies the components of community interventions for mental health and can contribute to a better implementation of these strategies. It also articulates autonomous community processes with strategies developed in health services. © 2023 John Wiley & Sons Ltd.